1976
DOI: 10.3133/pp813e
|View full text |Cite
|
Sign up to set email alerts
|

Summary appraisals of the nation's ground-water resources – California region

Abstract: Most people in the California Region live in a semiarid or arid climate, with precipitation less than the potential evapotranspiration-environments of perennial water deficiency. The deficiency becomes most onerous during the characteristically rainless summers and during recurrent droughts that may continue for 10--20 years. However, water from winter rain and snow can be stored for use during the dry summer months, and water stored during a wet climatic period can be used in a succeeding dry period; moreover… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
10
0

Year Published

1978
1978
2005
2005

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 13 publications
(10 citation statements)
references
References 12 publications
0
10
0
Order By: Relevance
“…The simulations indicated that vertical leakance greatly increased from the predevelopment values as a result of water flowing through some of the more than 100,000 irrigation well casings which are open to different aquifer layers. (Thomas and Phoenix, 1976). Thus, agricultural development in the valley is dependent on water from sources other than direct precipitation.…”
Section: Introductionmentioning
confidence: 99%
“…The simulations indicated that vertical leakance greatly increased from the predevelopment values as a result of water flowing through some of the more than 100,000 irrigation well casings which are open to different aquifer layers. (Thomas and Phoenix, 1976). Thus, agricultural development in the valley is dependent on water from sources other than direct precipitation.…”
Section: Introductionmentioning
confidence: 99%
“…Duell (1987) reviewed the available ground-water-quality data for the Antelope Valley for the purpose of designing a water-quality monitoring network. Land subsidence in the Antelope Valley resulting from ground-water withdrawals for agricultural, municipal, and industrial water use was reported by Lewis andMiller (1968), McMillan (1973), Thomas andPhoenix (1976), Holzer (1984), and Blodgett and Williams (1992). As early as 1947, the California Department of Water Resources (1947), California Department of Public Works (1955) and Snyder (1955) documented that the annual ground-water pumpage in Antelope Valley exceeded the estimated average annual ground-water recharge.…”
Section: Previous Studiesmentioning
confidence: 86%
“…This practice restricted agriculture to lands in the vicinity of major surface-water supplies (California Department of Water Resources, 1982, p. 25-27). The discovery of gold in the Sierra Nevada in January 1848 accelerated the influx of settlers (Thomas and Phoenix, 1976, p. E10) and, with this influx, the development of water resources. Reservoirs and widespread networks of ditches and flumes were built to divert water from streams at higher elevations and to sluice the goldbearing deposits.…”
Section: Distribution Systemsmentioning
confidence: 99%